2017
DOI: 10.1073/pnas.1702078114
|View full text |Cite
|
Sign up to set email alerts
|

Extinction risk is most acute for the world’s largest and smallest vertebrates

Abstract: Extinction risk in vertebrates has been linked to large body size, but this putative relationship has only been explored for select taxa, with variable results. Using a newly assembled and taxonomically expansive database, we analyzed the relationships between extinction risk and body mass (27,647 species) and between extinction risk and range size (21,294 species) for vertebrates across six main classes. We found that the probability of being threatened was positively and significantly related to body mass fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
257
5
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(287 citation statements)
references
References 52 publications
21
257
5
4
Order By: Relevance
“…Although certain small rodent clades are at risk of being lost entirely to extinction, imperilled species are distributed throughout the rodent phylogeny ( Figure 6b). These findings provide further evidence that not all species are at equal risk of extinction (Ohlemüller et al, 2008;Ripple et al, 2017). Although most ecological categories experience some degree of loss, the greatest impacts are felt by medium-sized rodents, rodents at higher trophic levels and rodents occupying higher elevation habitats in the tropics (Figure 6d).…”
Section: Conserving Species Ecological Diversity and Evolutionarymentioning
confidence: 69%
“…Although certain small rodent clades are at risk of being lost entirely to extinction, imperilled species are distributed throughout the rodent phylogeny ( Figure 6b). These findings provide further evidence that not all species are at equal risk of extinction (Ohlemüller et al, 2008;Ripple et al, 2017). Although most ecological categories experience some degree of loss, the greatest impacts are felt by medium-sized rodents, rodents at higher trophic levels and rodents occupying higher elevation habitats in the tropics (Figure 6d).…”
Section: Conserving Species Ecological Diversity and Evolutionarymentioning
confidence: 69%
“…Additionally, to account for the effect of species traits we explore the relationship between population growth rates and body mass, which is a correlate of many species traits (Brook et al., ; Hilbers et al., ). Recent research has shown there is a significant relationship between vertebrate body mass and extinction risk, such that heavier species of birds and mammals are likely to be more at risk of extinction (Ripple et al., ). We therefore hypothesized that larger bodied birds and mammals are more likely to have declining populations.…”
Section: Introductionmentioning
confidence: 99%
“…(1) discuss the biodiversity crisis in their reply to our article "Extinction risk is most acute for the world's largest and smallest vertebrates" (2). We agree with Kalinkat et al…”
mentioning
confidence: 53%
“…However, small vertebrates that use terrestrial habitats exclusively or in combination with freshwater habitats also have a greatly elevated risk of extinction (figure S3 in ref. 2). Indeed, our data show that 59% (76 of 128) of terrestrial vertebrate species with body masses ≤ 0.001 kg are threatened compared with 16% (1,965 of 12,015) for all terrestrial vertebrate species.…”
mentioning
confidence: 63%
See 1 more Smart Citation